2021
DOI: 10.33448/rsd-v10i2.12956
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Enteroccocus faecalis counts produced by three file systems in severely curved canals

Abstract: Aim: This study evaluated the effectiveness of the mechanical reduction of intracanal bacteria produced by the endodontic systems Reciproc Blue (VDW GmbH), XP-Endo Shaper (FKG Dentaire) and ProTaper Next (Dentsply Sirona Endodontics) in severely curved canals by culture analysis. Methodology: Fifty severely curved mesiobuccal canals of mandibular molars were selected and instrumented. Following this, six specimens were selected as control, while 44 canals were contaminated with Enterococcus faecalis strains (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
2
0
1
Order By: Relevance
“…Otero et al [30] also found that ProTaper Gold showed superior bacterial reduction compared to WaveOne Gold. Moreover, Nascimento et al [10] reported that the Reciproc Blue file system exhibited lower antibacterial action when compared to the ProTaper Next file system. These results can be attributed to the fact that the ProTaper file system removes the dentin surface more aggressively therefore leading to lower bacterial counts in samples after instrumentation [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Otero et al [30] also found that ProTaper Gold showed superior bacterial reduction compared to WaveOne Gold. Moreover, Nascimento et al [10] reported that the Reciproc Blue file system exhibited lower antibacterial action when compared to the ProTaper Next file system. These results can be attributed to the fact that the ProTaper file system removes the dentin surface more aggressively therefore leading to lower bacterial counts in samples after instrumentation [8].…”
Section: Discussionmentioning
confidence: 99%
“…Various improved nickel-titanium instrumentation systems with different characteristics have been developed to improve the procedure of intracanal bacterial reduction [9,10]. The ProTaper Gold (Dentsply Maillefer, Ballaigues, Switzerland) file system is produced using M-Wire technology and employs a continuous rotational movement.…”
Section: Introductionmentioning
confidence: 99%
“…O principal objetivo da terapia endodôntica é o completo selamento do sistema de canais radiculares, para prevenir e tratar a periodontite apical. Muitos fatores têm sido relacionados com o insucesso neste processo, dos quais podemos realçar a permanência da infecção microbiana dentro dos canais radiculares, a complexidade anatômica, irregularidades na dentina, instrumentação e obturação inadequadas (Roças et al, 2016;Nascimento et al, 2021).…”
Section: Introductionunclassified